The effect of 12-week high-dose Colostrum Bovinum supplementation on immunological, hematological and biochemical markers in endurance athletes: a randomized crossover placebo-controlled study - Durkalec-Michalski, Krzysztof; Główka, Natalia; Podgórski, Tomasz; Woźniewicz, Małgorzata; Nowaczyk, Paulina M. (Frontiers in Immunology, 2024)
Background: Bovine colostrum (COL) is assumed to be one of the strongest natural immune stimulants. Regular ingestion of COL may contribute to improved immune response in athletes exposed to high training loads. Methods: Twenty-eight endurance-trained males aged 31.1±10.2 years (body mass 81.9±9.0 kg; height 1.82±0.06 m) completed this randomized double-blind placebo(PLA)-controlled crossover study aimed at investigating the effect of 12-week COL supplementation (25gCOL•day -1 ) on resting (REST), exercise-induced (POST-EX), and short-term post-exercise recovery (REC; 1 h after test exercise) changes in selected saliva and blood immunoglobulins (Ig), white blood cell (WBC) count and differential; as well as blood hematological, nutritional status and muscle damage indices. The protocol assumed 4 study visitsbefore/after supplementation with COL (COLPRE and COLPOST) and PLA (PLAPRE and PLAPOST). During testing sessions, incremental rowing test to exhaustion and swimming-specific performance test were introduced as exercise stimuli. Results: At COL POST visit the secretory IgA (SIgA) concentration in saliva was significantly higher at POST-EX and REC compared to REST (p<0.05). COL supplementation had no effect on blood IgA, IgE, IgD, IgG, and IgM concentrations. Furthermore, after COL supplementation decrease of hematocrit at REC (p<0.05) was revealed. Conclusions: 12-week supplementation with 25 gCOL•day -1 in endurance-trained male athletes resulted in a favourable increase in post-exercise concentration of salivary SIgA. COL seems to be a potential stimulator of local immune defence after exercise-induced homeostasis disturbances. Nevertheless, the lack of effect on blood markers indicates the need for further research in the area of mechanisms underlying the effect of the supposed COL immunological capacity.